Genetic association of MIR-449B, GCLC, eNOS, SORD, and ENPP1 with diabetic retinopathy - Xu, Huijuan; Fan, Lin; Luo, Huaichao; Ju, Xueming; Li, Huan; Rong, Shisong; Yuan, Ye; Xiao, Jialing; Zhang, Ruifan; Wang, Kaifang; Zou, Rong; Hao, Fang; et al. (Experimental eye research, 2025)
Identifying the genetic risk factors of diabetic retinopathy (DR) is essential for discovering the potential pathogenesis of DR. This study determined the association of DR with five single nucleotide polymorphisms (SNPs) specifically in type 2 diabetes mellitus (T2DM) patients, including rs10061133(MIR-449B), rs17883901(GCLC), rs2070744(eNOS), rs3759890 (SORD) and rs7754561 (ENPP1). A total of 1433 individuals were enrolled in this study, comprising healthy controls (ctrls = 480), individuals with diabetes mellitus without retinopathy (DNR = 480), non-proliferative DR(NPDR = 378), and proliferative DR(PDR = 95). The five SNPs were genotyped utilizing Mass ARRAY MALDI-TOF technology. Odds ratio (OR) and 95% confidence intervals (95% CI) were calculated for the risk of genotype and allele. We performed a literature search in PubMed published before July 16, 2023. The Newcastle Ottawa Scale was used to evaluate the overall quality of the case-control studies. Consequently, we found that there were statistically significant differences between PDR cases and healthy controls for rs10061133 (P = 0.007, OR = 1.59, 95% CI = 1.32–2.23) and rs17883901 (P = 0.020, OR = 1.67, 95% CI = 1.08–2.57), rs17883901 was significantly associated with NPDR (P = 0.023, OR = 1.39, 95% CI = 1.05–1.85), there was a significant association between DR cases and healthy controls (P = 0.048, OR = 1.22, 95% CI = 1.00–1.48) for rs3759890 in the allelic model. DR show no relationships with the other two SNPs compared to healthy controls. In multivariate analyses comparing the DR and DNR groups, rs7754561(A), rs10061133(G), and rs17883901(A) were identified as risk loci for DR in individuals with a duration of diabetes of ≥5 years (P = 0.0023, P = 0.0037, and P = 0.0376, respectively). Furthermore, individuals carrying rs10061133(G) exhibited a higher risk of DR in the hyperglycemic group (glucose ≥8 mmol/L). Secondly, we showed that one polymorphism in eNOS (rs2070744, T > C) showed a suggestive association with DR in the meta-analysis (allelic model:P < 0.05, OR = 1.18, 95% CI: 1.07–1.30, Z = 3.46, I2 = 34%). Subsequently, including studies that used either healthy subjects or diabetic subjects without DR as controls, the association of eNOS rs2070744 with DR was consistently significant (P = 0.002) and exhibited intermediate heterogeneity (I2 = 48%). Furthermore, polymorphisms in GCLC (rs17883901) and SORD (rs3759890) were also associated with DR, with P-values of 0.004 (I2 = 93%) and 0.03 (I2 = 3%), respectively, suggesting their potential involvement in the disease. In conclusion, this study documented that rs10061133(G), rs17883901(A), and rs3759890(G) could be the independent risk factors for retinopathy in Chinese patients with T2DM, offering a foundation for genetic risk assessment in clinical practice. Furthermore, our meta-analysis reveals a significant association between rs2070744 and DR, implying the potential involvement of the MIR-449B, GCLC, SORD, and eNOS variants in the development of DR, which could be a promising direction for developing new treatments aimed at mitigating the risk of DR in susceptible populations. •Identified SNPs in MIR-449B, GCLC, and SORD as risk factors for DR in the Chinese Han population, highlighting their roles.•Found significant associations of rs10061133 and rs17883901 with PDR, suggesting their potential as genetic indicators.•Demonstrated rs17883901's link with NPDR, highlighting its potential as an early-stage DR marker.•Uncovered eNOS gene polymorphism (rs2070744) association with DR, emphasizing its relevance in different study groups.•Multivariate analysis revealed associations of these SNPS with DR, considering sex, duration and glucose levels.